Acute Abdomen: Clinical Mimickers Across Multisystem Diseases - Araujo-Filho, Irami; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Acute abdominal pain is a common reason for emergency department visits and often involves multisystem diseases that mimic the acute abdomen, affecting diagnostic accuracy and patient management. Many of these conditions reproduce classic surgical signs with remarkable precision, originating from diverse systems, including endocrine, metabolic, hematologic, infectious, vascular, neurologic, gynecologic, and thoracic pathways, leading to significant diagnostic overlap. Recognizing these multisystem mimickers is essential for reducing misdiagnosis, unnecessary surgeries, and delays in identifying life-threatening conditions. This review aims to synthesize the current evidence on multisystem clinical diseases presenting as acute abdomen, covering epidemiology, mechanisms, clinical features, diagnostic challenges, and management strategies to improve differentiation between surgical and non-surgical causes. Evidence was examined across multiple specialties to create a unified, interdisciplinary diagnostic framework emphasizing pathophysiology, clinical reasoning, and emergency decision support. Analysis revealed extensive heterogeneity among clinical mimickers, with recurrent themes including misleading peritoneal signs, systemic inflammatory responses, atypical imaging findings, and overlapping metabolic and vascular abnormalities. These conditions often lead to diagnostic uncertainty, delayed therapeutic action, and unnecessary surgical procedures. Multisystem integration, pattern recognition, and early use of targeted diagnostic tools were identified as key strategies to improve accuracy. Clinical diseases that mimic acute abdomen constitute a complex, underrecognized group of conditions with significant implications for emergency surgical decision making. An integrated mechanism-based approach is essential to enhance diagnostic precision, reduce negative laparotomies, and improve patient outcomes.